2020
DOI: 10.1192/j.eurpsy.2019.17
|View full text |Cite
|
Sign up to set email alerts
|

The role of schizotypal traits and the OXTR gene in theory of mind in schizophrenia: A family-based study

Abstract: Background. There is consistent evidence that theory of mind (ToM) is impaired in schizophrenia (SZ); however, it remains unclear whether such deficits are trait- or state-dependent. We evaluated ToM in patients with schizophrenia spectrum disorders (SSDs), their healthy first-degree relatives, and controls to test its suitability as an endophenotypic marker. We also studied the modifying effect of markers of clinical and genetic liability to SZ (schizotypy and genetic variability in the oxytocin receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Afterward, correlation analyses were performed to confirm four IDEGs, in which there are three genes ( NPY , OXTR , and FGF12 ) related to SZ supported by previous studies ( 26 , 44 ). Such a result also clearly demonstrates the reliability of this study method.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Afterward, correlation analyses were performed to confirm four IDEGs, in which there are three genes ( NPY , OXTR , and FGF12 ) related to SZ supported by previous studies ( 26 , 44 ). Such a result also clearly demonstrates the reliability of this study method.…”
Section: Discussionmentioning
confidence: 75%
“…When oxytocin receptors are antagonized, social fear of mice is increased ( 49 ). And studies also found that the polymorphism variation of the OXTR is related to nerve development disorders such as SZ ( 44 ). Furthermore, there have been no relevant studies about the relationship between SZ and FGF12 , BLNK.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On a genetic basis, the involvement of single-nucleotide polymorphisms of the oxytocin gene (OXT) in schizophrenia vulnerability has been proven [224]. In addition, singlenucleotide polymorphisms of the oxytocin receptor gene (OXTR) are also associated with a risk of schizophrenia [225], and a relationship with clinical symptomatology in schizophrenia, including general psychopathology [226], negative symptoms [224], social cognition [227,228], and the treatment response with antipsychotics for positive symptoms [226], has been more clearly elucidated. The single-nucleotide polymorphisms of the oxytocin receptor gene could profoundly affect treatment-refractory symptoms by mediating social cognitive processes in persons with schizophrenia [217].…”
Section: The Implication Of Oxytocin In Schizophreniamentioning
confidence: 99%
“…This study aimed to investigate whether the oxytocin receptor gene ( OXTR ), a gene involved in the ability to understand others’ intention ( Gong et al. , 2017a ; Giralt-Lopez et al. , 2020 ), is related to intent-based moral judgment.…”
Section: Introductionmentioning
confidence: 99%